The Role of nutrition management in the treatment of acute pancreatitis – comprehensive review - Kazzi, Marcel; Bieniasz, Jan; Dendys, Konrad; Puła, Michał; Wychota, Marta (Journal of Education, Health and Sport, 2023)
Introduction and purpose The treatment of acute pancreatitis remains a clinically significant problem worldwide, as well as in Poland, where the incidence of the condition is nearly twice as high as in the global population. The aim of this study is to present the latest available guidelines regarding conservative management of patients diagnosed with acute pancreatitis, focusing on nutritional management and treatment methods. Materials and methods: The literature available in PubMed, Scopus, Google Scholar databases, and guidelines from the European Society for Clinical Nutrition and Metabolism (ESPEN) was reviewed using the following keywords: "acute pancreatitis," "AP treatment," "nutritional treatment of acute pancreatitis," "enteral nutrition," "parenteral nutrition." Description of the state of knowledge: The approach to conservative treatment for acute pancreatitis has evolved over the years. Previously, the preferred route of feeding was parenteral with limited lipid content, aimed at reducing the stress on the pancreas. Current guidelines emphasize the superiority of enteral nutrition using a complete nutritional composition. Conclusions: The latest guidelines highlight the advantage of enteral nutrition over parenteral nutrition, with implementation within 48 hours of diagnosis. This approach reduces mortality, the risk of complications, and the duration of hospital stay for patients. The appropriate caloric intake should be adjusted to the individual needs of the patient, considering the severity of the disease and coexisting conditions. Meeting the patient’s energy requirements, along with the choice of administration method and precise composition of nutritional formulas, play a crucial role in therapy.